ePortfolios at the School of Education: Curtin University of Technology. - Dixon, Kathryn; Pelliccione, L. (2009)
Many universities are currently undergoing curriculum reform and individual courses are also developing their own set of student attributes/outcomes in line with their wider organisational graduate attributes. However, in many cases universities and individual courses do not have a structure in place to map student progress against these outcomes. Curtin University of Technology, which is the focus of this research, has implemented the use ofstudent ePortfolios in its undergraduate Bachelor of Education Program. The School of Education envisages that the ongoing utilisation of ePortfolios will streamline and illuminate more transparent assessment and evaluation procedures at the institutional and course level as well as meeting the requirements of professional bodies. They provide a vehicle for: • measuring the quality of courses • the development of the individual student • the effectiveness of individual teaching • the appropriateness and value of the attributes and outcomes themselves.The major advantage of an ePortfolio approach in a systematic manner throughout the duration of an undergraduate degree is that students’ achievements can be readily mapped against current employment requirements in a very practical, transportable and transparent sense. This presentation will focus on the implementation process of ePortfolios by teacher education students at Curtin University of Technology in Western Australia. Student examples will be shown and reflective guidelines, as well as assessment tools will be shared with participants. Successes and challenges of the past five years will also be highlighted.